Genomic evolution and dissemination of non-conjugative virulence plasmid of ST65 carbapenem-resistant and hypervirulent Klebsiella pneumoniae strains in a Chinese hospital - Tian, Dongxing; Zhao, Mingqi; Liu, Lihua; Lu, Shuhua; Dong, Haixin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe global rise in infections caused by hypervirulent and carbapenem-resistant K. pneumoniae (CR-hvKp) represents a growing public health threat. This study investigates ST65 CR-hvKp strains, with a focus on their genomic attributes and the mechanisms underlying the transmission of non-conjugative virulence plasmids.MethodsTwo clinical K2-ST65 CR-hvKp isolates (P6 and P10) were identified. Plasmid conjugation experiments were performed to assess the dissemination of the virulence plasmid. Antimicrobial susceptibility testing and virulence assays, including serum resistance, siderophore production, and G. mellonella larvae infection models, were used to characterize resistance and virulence phenotypes. Comprehensive bioinformatic analyses were performed to explore genetic evolution.ResultsGenomic analyses showed that both P6 and P10 carry a non-conjugative virulence plasmid, a conjugative untyped KPC plasmid, and a conjugative IncM2 plasmid. These isolates displayed broad-spectrum anti-microbial resistance and multiple virulence phenotypes, although they failed to sustain both hypervirulence and carbapenem resistance over time. The IncM2 plasmid was shown to be essential for the transfer of non-conjugative virulence plasmid. Mechanistic studies highlighted IS26-mediated plasmid fusion and the role of IncM2 plasmids in mobilizing non-conjugative virulence plasmids. The resulting transconjugants exhibited multidrug resistance, enhanced capsule production, and increased siderophore production.ConclusionsThis study provides new insights into the genomic dynamics of ST65-CR-hvKp strains and uncovers key mechanisms, such as IS26-mediated plasmid fusion and IncM2-mediated mobilization, which facilitate the dissemination of non-conjugative virulence plasmids. Understanding these mechanisms is crucial for developing effective strategies to manage and prevent the spread of these clinically challenging strains.